Integracija kvantitativne in kvalitativne metodologije v raziskavah v zdravstvu - Zurc, Joca (Zdravstveno varstvo, 2013)
Background: The popularity of integrating quantitative and qualitative methodologies in the same research has grown incredibly in recent years. There is a lack of evidence about the efficiency of mixed methods use in health sciences research practice. The purpose of this study was to analyse the areas, main research themes, mixed methods research design typologies and efficiency of implementation and further open questions regarding mixed methods in health sciences. Methods: A systematic review was made on a sample of 25 scientific articles of health sciences that stated mixed methods use in research. Inclusion criteria: original scientific article with applying and evaluating of mixed methods, published during the period July 2006 - July 2011 in a peer reviewed journal, included in international databases: WebSurveyMethodology, CINAHL, MEDLINE and PubMed. Results: All 25 studies provided effectiveness of mixed methods use in health science research practice. Mixed methods are the most popular in nursing (32%) and health promotion (28%). Sequential mixed methods research design is prevalent (64.3%), with the first research phase in priority (71.4%). The relation between quantitative (57.2%) and qualitative (42.8%) priority approach is balanced. Complementarity (57.1%), triangulation (28.6%) and expansion (14.3%) are the most common research purposes for using mixed methods in health sciences. Conclusions: The presented findings confirmed mixed methods applicability for the complex and less studied research problems in health sciences. Conceptualisation of mixed methods in different disciplines of health sciences, development of quality criteria and standards for mixed methods research assessment and expansion of mixed methods in clinical practice as support in evidence based practice development appeared as the most important research questions of mixed methods in health sciences that should be addressed in the future studies.
Keywords: evalvacija; Evalvacije; health care; Kakovost; Zdravstvena nega; zdravstvo; znanstveni članki